1999
DOI: 10.1079/wps19990009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of egg of origin and chick post-hatch nutrition on broiler live performance and meat yields

Abstract: The weight of hatching eggs can influence broiler live performance regardless of hen age. Egg composition is altered with egg weight, but such alterations do not seem to have major effects on broiler growth and processing yields. The chick hatches with a yolk sac which provides nutrients for the transition to independent feeding. Alterations in egg weight and composition do not affect the proportion of yolk sac to body weight as much as its composition, particularly with eggs from very young hens. The contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 112 publications
3
64
0
14
Order By: Relevance
“…Sterling et al (2002) found that young chicks, beside the high nutritional requirements of protein and essential amino acids, are more sensitive to the presence of antinutritional substances in feed. The physiological background might be related to incomplete development of the gastrointestinal tract (Wijtten et al, 2004), which affects the digestion efficiency in the consecutive growing phases (Vieira and Moran, 1999;Ravindran, 2002). Such findings agree with our results where the depressive effect of the faba bean in starter diets was partially compensated in the following growing phases.…”
Section: Resultsmentioning
confidence: 99%
“…Sterling et al (2002) found that young chicks, beside the high nutritional requirements of protein and essential amino acids, are more sensitive to the presence of antinutritional substances in feed. The physiological background might be related to incomplete development of the gastrointestinal tract (Wijtten et al, 2004), which affects the digestion efficiency in the consecutive growing phases (Vieira and Moran, 1999;Ravindran, 2002). Such findings agree with our results where the depressive effect of the faba bean in starter diets was partially compensated in the following growing phases.…”
Section: Resultsmentioning
confidence: 99%
“…The post-hatching chick needs to adapt from maternal nutrition to exogenous feed, when nutrient supply changes from the high fat yolk sac to a high starch feed, and this process may take several days (Vieira & Moran, 1999). During this period, the secretion of endogenous enzymes also changes according to the composition of the exogenous feed, together with an increase in digestive organ size to rapidly accommodate the increase in feed intake .…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Nir & Levanon (1993), a perda de peso imposta aos pintinhos que receberam ração após 40 a 52 horas de eclosão (12 e 24 horas pós-alojamento) atrasa de 1 a 2 dias, respectivamente, o tempo para que as aves atinjam o peso de abate das aves alimentadas logo após a eclosão. Atrasos de 24 horas no alojamento determinam perdas de peso inicial aos 49 dias de 110 g (Vieira & Moran, 1999a).…”
Section: Resultsunclassified